2016
DOI: 10.1371/journal.pntd.0005050
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Time of Admission among Notified Dengue Fever Cases in Region VIII Philippines from 2008 to 2014

Abstract: In cases of Dengue fever, late hospital admission can lead to treatment delay and even death. In order to improve early disease notification and management, it is essential to investigate the factors affecting the time of admission of Dengue cases. This study determined the factors associated with the time of admission among notified Dengue cases. The study covered the period between 2008 and 2014 in Region VIII, Philippines. The factors assessed were age, sex, hospital sector, hospital level, disease severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…This can emphasizes practice of early admission among children patient. [11] There are earlier study that showed Free NS1 levels in plasma correlated with viremia levels and were higher in patients with DHF than in those with DF. An elevated free NS1 level (≥600 ng/mL) within 72 hours of illness onset identified patients at risk for developing DHF, Immune complex formation with secreted (sNS1) and sNS1 binding to endothelial cells have been proposed as potential factors in DHF pathogenesis.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…This can emphasizes practice of early admission among children patient. [11] There are earlier study that showed Free NS1 levels in plasma correlated with viremia levels and were higher in patients with DHF than in those with DF. An elevated free NS1 level (≥600 ng/mL) within 72 hours of illness onset identified patients at risk for developing DHF, Immune complex formation with secreted (sNS1) and sNS1 binding to endothelial cells have been proposed as potential factors in DHF pathogenesis.…”
Section: Discussionmentioning
confidence: 91%
“…This phenomenon especially occurs in regions with a high incidence of DHF cases. [11] Other study in Southeast Asia found that cases of dengue adults showed mild signs and symptoms. [12] In contrast, a majority of the severe cases occur in children aged 2-15 years.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Because many clinically severe cases did not qualify as DHF, new guidelines were issued in 2009, now grouping cases into dengue without warning signs, dengue with warning signs (DWWS), and severe dengue (SD) that includes DSS (WHO 2009a). The advantages of the new classification have been discussed (Abello et al 2016, da Silva et al 2018; however, the 1997 classification remains in use among some clinicians and in literature.…”
mentioning
confidence: 99%